The Principle of Equality Before the Law in Indonesian Corruption Case: Is It Relevant? - Moh. Iqra Syabani Korompot; Sholahuddin Al-Fatih; David Pradhan (Lembaga Contrarius Indonesia, 2021)
Article 28D paragraph (1) of the NRI Constitution of 1945 states that